Cardiotoxicity: A Major Setback in Childhood Leukemia Treatment. (8th January 2021) - Lazăr, Diana R.; Farcaş, Anca D.; Blag, Cristina; Neaga, Alexandra; Zdrenghea, Mihnea T.; Căinap, Călin; Lazăr, Florin L.; Stef, Adrian; Căinap, Simona S.
Abstract : Ongoing research in the field of pediatric oncology has led to an increased number of childhood cancer survivors reaching adulthood. Therefore, ensuring a good quality of life for these patients has become a rising priority. Considering this, the following review focuses on summarizing the most recent research in anthracycline-induced cardiac toxicity in children treated for leukemia. For pediatric cancers, anthracyclines are one of the most used anticancer drugs, with over half of the childhood cancer survivors believed to have been exposed to them. Anthracyclines cause irreversible cardiomyocyte loss, leading to chronic, progressive heart failure. The risk of developing cardiotoxicity has been known to increase with the treatment-free interval and total cumulative dose. However, because of individual variations in anthracycline metabolism, it has recently been shown that there is no risk-free dose. Moreover, studies have shown that diagnosing anthracycline-induced cardiomyopathy in the symptomatic phase is associated with poor treatment response and prognosis. Thus, early and systematic evaluation of these patients is crucial to allow optimal therapeutic intervention. Although currently echocardiographic assessment of left ventricle ejection fraction and cardiac biomarker evaluation are being used for cardiac function monitoring in oncologic patients, there is no established follow-up and treatment protocol for these patients, and these methods are neither specific nor sensitive for identifying early cardiac dysfunction. All things considered, the need for ongoing research in the field of pediatric cardiooncology is crucial to offer these patients a chance at a good quality of life as adults.